2022
DOI: 10.3389/fpsyg.2022.814154
|View full text |Cite
|
Sign up to set email alerts
|

Employee Growth Mindset and Innovative Behavior: The Roles of Employee Strengths Use and Strengths-Based Leadership

Abstract: This study aimed to investigate the relationship of employee growth mindset with innovative behavior and the mediating role of use of strength as well as the moderating role of strengths-based leadership in this relationship. Data with a sample of 244 employees working in diverse Chinese organizations were collected at two points in time. Results of bootstrapping analyses demonstrated that growth mindset is positively related to innovative behavior, employee strengths use partially mediates the positive relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Beyond demographics, other stable person-level factors such as proactive personality (Yi Feng-Chen et al ., 2021) and growth mindset (Liu and Tong, 2022) have been previously connected to strengths use but were not included in our study. Future research could overcome this limitation by modeling such person-level factors as predictors or moderators to understand better how the proactive mechanisms work in the context of such inter-individual differences.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond demographics, other stable person-level factors such as proactive personality (Yi Feng-Chen et al ., 2021) and growth mindset (Liu and Tong, 2022) have been previously connected to strengths use but were not included in our study. Future research could overcome this limitation by modeling such person-level factors as predictors or moderators to understand better how the proactive mechanisms work in the context of such inter-individual differences.…”
Section: Discussionmentioning
confidence: 99%
“…As an individual employee factor, employee engagement not only brings rich innovation inspiration to employees but also to enterprises and organizations and improves their creativity. Although existing studies have shown that employee positive work emotions, recognition and commitment to work can promote the performance of employee innovative behaviours (Lee et al, 2016;Jung and Yoon, 2018;Nathan et al, 2019;Liu and Tong, 2022), the research on employee engagement mostly centre on exploring antecedent variables and their impact on job performance, seldom explores its impact on open service innovation (Kwon and Kim, 2020), it is hard to determine how it affects the specific mechanism of open service innovation. In addition, some studies began to focus on the important function of employee psychological motivation, and the mediating of selfefficacy gradually became a new research hotspot (Zhao et al, 2022).…”
Section: Introductionmentioning
confidence: 99%